Methodological approaches to the land inventory within land management require changes - Dorosh, Y.; Tarnopolskyi, A.; Avramchuk, B. (Land Management, Cadastre and Land Monitoring, 2019)
On the basis of the conducted researches it was clarified that the current legislative and regulatory acts regulating the carrying out of works on inventory of land under land management can not be applied equally to all objects of land management with peculiarities of use for the intended purpose. At the present time, in the field of land management there has been a situation in which the implementation of land management, in the sense of a set of measures aimed at the rational use of land, almost does not occur, but the whole land management system is reduced to the implementation of works related to registration of land plots, restrictions on their use, registration real rights to them, and encumbrances. It is substantiated that for scientific institutions, organizations and agricultural enterprises with special features of land use there is a need for the development of different methods during carrying out this type of work with a clear definition of the stages of such works. It is proved that the introduction of this methodology will allow to provide a systematic approach to the work of inventorying the lands of scientific institutions, organizations or agricultural enterprises in land management, taking into account the features of land use, depending on the specificity of use, unifying their content and improving the quality. Keywords: inventory, land cadastre, land management, topographical and geodetic surveys, land type, legal status of lands.